Building a compassionate workplace using information technology: Considerations for information systems research. (February 2021) - Chatterjee, Sutirtha; Chakraborty, Suranjan; Fulk, H. Kevin; Sarker, Suprateek
Highlights: Proposes the need for information systems (IS) researchers to pursue work on compassion in organizational workplaces. Highlights the value of IS research on compassion. Discusses how information technology (IT) is intricately related to compassionate phenomena in workplaces. Proposes an integrative framework that maps the scope of organizational compassion in IS. Develops a research agenda that can aid future inquiry into compassion in IS research.. Abstract: This opinion paper presents the need for IS research on compassion in the organizational workplace. Given the current challenges caused by COVID-19, we argue that organizations need to be resilient to counter the adverse effects of this pandemic. Developing a compassionate organizational workplace is an effective way to build resilient organizations. The paper draws attention to the fact that a focus on compassion can be a valuable scope of inquiry within IS research. It proposes an integrative framework mapping the scope of compassion in IS research and develops a research agenda that can aid future inquiry into this phenomenon.